2020
DOI: 10.1590/1806-9282.66.s2.65
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of favipiravir on hematological parameters of covıd-19 patients

Abstract: SUMMARY INTRODUCTION This study aims to evaluate changes in hematological parameters after the follow-up of patients who received treatment with favipiravir due to COVID-19 infections. METHODS Sixty-two cases receiving favipiravir treatment for at least five days due to COVID-19 infection were evaluated retrospectively. Parameters including age, gender, nasopharyngeal swab positivity, and chronic diseases were analyzed. Hematologic parameters were analyzed before and after the treatment. RESULTS The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
12
0
2
Order By: Relevance
“…Among the 11 studies, three studies were RCTs [16,[18][19][20], one study was a non-randomized controlled study [17], one study was a before and after nonrandomized controlled study [21], and six studies were observational studies or case series [22][23][24][25][26]. Among the comparative studies, the comparators included umifenovir [17], baloxavir marboxil [18], standard of care (SOC) [19], lopinavir/ritonavir [21], and HQ alone or in combination with azithromycin [25].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Among the 11 studies, three studies were RCTs [16,[18][19][20], one study was a non-randomized controlled study [17], one study was a before and after nonrandomized controlled study [21], and six studies were observational studies or case series [22][23][24][25][26]. Among the comparative studies, the comparators included umifenovir [17], baloxavir marboxil [18], standard of care (SOC) [19], lopinavir/ritonavir [21], and HQ alone or in combination with azithromycin [25].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…According to the same study, although the white blood cell count did not change after taking favipiravir, the platelet count increased significantly. 14 In this study, anaemia was observed in 16.2%, neutropenia in 3.5% and thrombocytopenia in 2.6% of patients after favipiravir treatment.…”
Section: Discussionmentioning
confidence: 50%
“…We recently showed that the using of standardized dose of FVP for five days reduced the erythroid series as side effects in a small study involving 62 COVID-19 positive patients (22). Also, FVP related hyperuricemia was reported previously (23).…”
Section: Discussionmentioning
confidence: 60%